2003
DOI: 10.1189/jlb.0703319
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated alterations in the recruitment of signal-transduction proteins to lipid rafts in human T lymphocytes

Abstract: Aging is associated with a decline in T cell activation and proliferation, but the underlying mechanisms are not fully understood. Recent findings suggest that lipid rafts act as a platform in the initiation of T cell activation by selectively recruiting signaling proteins associated with formation of the initial complex of signal transduction. We tested the hypothesis that lipid raft properties are altered in T lymphocytes from elderly, healthy individuals in comparison with young subjects. Results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 62 publications
3
91
0
Order By: Relevance
“…We have already shown that the activation of Lck, ERK, and Akt in T cells is altered with aging (Fülöp et al 2012;Larbi et al 2004b). We therefore investigated whether the phosphorylation status of these key signaling molecules can be modulated by HDL to explain the functional effects described above.…”
Section: Effect Of Hdl On Tcr-mediated Signalingmentioning
confidence: 92%
“…We have already shown that the activation of Lck, ERK, and Akt in T cells is altered with aging (Fülöp et al 2012;Larbi et al 2004b). We therefore investigated whether the phosphorylation status of these key signaling molecules can be modulated by HDL to explain the functional effects described above.…”
Section: Effect Of Hdl On Tcr-mediated Signalingmentioning
confidence: 92%
“…Other receptors/molecules are located in the peripheral SMAC and migrate into the cSMAC to regulate activation (39). Here, only the signaling molecules/pathways that are known to display age-related changes are shown (53). CD4-or CD8-associated Lck recruits and activates Zeta-associated protein of 70 kDa (ZAP-70) and phospholipase C␥-1 (PLC␥-1) on exclusion of CD45.…”
Section: T-cell Function Activation and Signaling At The Cellular Lmentioning
confidence: 99%
“…The last is associated with several molecules including Vav, influencing cytoskeletal rearrangements (22). Together, these changes in expression (E), phosphorylation (P), or recruitment (R) cause differential activation of mitogen-activated protein kinases (MAPK) and translocation of transcription factors including NF-B, NF-AT, and AP-1 into the nucleus (53,54). This is decreased in aged T-cells and directly affects clonal expansion due to decreased IL-2 production.…”
Section: T-cell Function Activation and Signaling At The Cellular Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have reported alterations in early signaling events in old mice (73) and in human T lymphocytes from elderly patients (74), furthering the common characteristics between ex vivo culture expansion and immuosenescence. Three major proteins, Lck, LAT, and ERK, were extracted from the model as having primary roles in accurately predicting cellular age.…”
Section: Discussionmentioning
confidence: 82%